2016
DOI: 10.1371/journal.pone.0164305
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrobiopterin Supplementation: Elevation of Tissue Biopterin Levels Accompanied by a Relative Increase in Dihydrobiopterin in the Blood and the Role of Probenecid-Sensitive Uptake in Scavenging Dihydrobiopterin in the Liver and Kidney of Rats

Abstract: Tetrahydrobiopterin (BH4) is an essential cofactor of nitric oxide synthase (NOS) and aromatic amino acid hydroxylases. BH4 and 7,8-dihydrobiopterin (BH2) are metabolically interchangeable at the expense of NADPH. Exogenously administered BH4 can be metabolized by the body, similar to vitamins. At present, synthetic BH4 is used as an orphan drug for patients with inherited diseases requiring BH4 supplementation. BH4 supplementation has also drawn attention as a means of treating certain cardiovascular symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…This investigation used SP instead of BH4 because SP is more permeable to cells (Ohashi et al, 2016). SP has not been used as extensively in the clinic as BH4, with only one reported study on its use in the treatment of atypical phenylketonuria due to BH4 deficiency (Curtius et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…This investigation used SP instead of BH4 because SP is more permeable to cells (Ohashi et al, 2016). SP has not been used as extensively in the clinic as BH4, with only one reported study on its use in the treatment of atypical phenylketonuria due to BH4 deficiency (Curtius et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the 80% suppression by PBC strongly suggested that the relevant transporters involved in the BH 4 uptake were mostly the organic anion transporters OAT1 and OAT3 which were reported to participate in the removal of various water-soluble compounds in plasma [ 30 32 ]. Although the involvement of other transporters in BH 4 removal was not ruled out, the near exclusive participation of the PBC-sensitive transporters in the removal was suggested, and it might be a prerequisite for the rapid release of these compounds to the urine at proximal tubules in rats as observed previously [ 21 , 22 , 29 ].…”
Section: Resultsmentioning
confidence: 96%
“…The experimental procedure using rats was almost the same as described in the previous paper [ 29 ] except that the rats did not receive 6RBH 4 . In brief, rats (SD, 8–10-week-old males) were loaded with PBC (200 mg/kg) under anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to this, BH 4 is an instable molecule that is easily oxidized to BH 2 , although it appears BH 2 is then intracellularly reconverted into BH 4. Overall, BH 4 supplementation does increase plasma BH 4 concentrations, albeit very inefficiently, but it is unclear to what extent BH 4 then crosses the blood‐brain barrier (BBB). At least in part, this question is prompted by the experience of BH 4 treatment in patients with BH 4 deficiency, resulting in a disturbed function of PAH, as well as of tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH).…”
Section: Bh4 and The Brainmentioning
confidence: 99%